Порівняльний аналіз підходів до оцінки інвестиційної привабливості будівельних організацій - Саламатіна, В. В. (Ways to Improve Construction Efficiency, 2012)
In the article, a comparative analysis of approaches to the evaluation of investment attractiveness of the construction organization.